(untitled) (Revista horizonte, 2015)
The research aimed; "Knowing whether pre - school children from the commune of Valdivia who have not received intervention of physical education teachers have a level of gross motor development according to their age. A descriptive quantitative approach with a non- experimental design was used transeccional court. The sample was not probabilistic judgment and formed a total of 53 preschools which were subjected to the test of gross motor development of TGMD-2. From the data collected, it was found that the level of gross motor development stood at 60.4 % in the age categories un der, poor and very poor, which invites us to rethink the presence of professionals of physical activity in this age group.